2000
DOI: 10.1002/(sici)1097-4636(2000)53:1<93::aid-jbm13>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Two-year clinical performance of two primer adhesives on Class V restorations

Abstract: The prime purpose of this clinical trial was to examine the clinical quality and retention rate of resin composite in connection with two recently developed acetone-based primer adhesives in Class V lesions according to ADA Clinical Protocol Guidelines for Dentin and Enamel Adhesive Materials. All cavities were nonretentive and predominantly in dentin (mixed Class V lesions). Total bonding was not limited either by sub-base or by base materials. All the trial restorations were placed under rubber dam. Group 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…With former adhesive systems, lost composite restorations composed up to 80% of the total restorations after four years. 17 Other studies confirmed that two-step etch-and-rinse adhesives have shown satisfactory retention rates (80% to 93%) during the first two years of evaluation, 4,26,27 but in the present study the number of lost restorations after seven years of clinical service was considerable. Evidence exists now that two-step etch-and-rinse adhesives are regarded as permeable membranes after polymerization because they lack a comparatively more hydrophobic bonding resin layer.…”
Section: Resultssupporting
confidence: 65%
“…With former adhesive systems, lost composite restorations composed up to 80% of the total restorations after four years. 17 Other studies confirmed that two-step etch-and-rinse adhesives have shown satisfactory retention rates (80% to 93%) during the first two years of evaluation, 4,26,27 but in the present study the number of lost restorations after seven years of clinical service was considerable. Evidence exists now that two-step etch-and-rinse adhesives are regarded as permeable membranes after polymerization because they lack a comparatively more hydrophobic bonding resin layer.…”
Section: Resultssupporting
confidence: 65%
“…The mean age of participants across studies was 52.9 (SD 6.0), although this did not take into account four studies where median age or age ranges were reported, [17][18][19][20] and three studies where age was not reported. 6,21,22 All patients were adult and had NCCLs, although Ritter et al 23 and Turkun 24 both included two lesions that had superficial areas of caries removed.…”
Section: Resultsmentioning
confidence: 99%
“…5,9,25,[28][29][30][31][32][33] In the past, one of the intentions of the authors of the current study was to combine the clinical assessment of enamel-dentin bonding systems with experimental in vivo and in vitro studies on the basis of the micromorphological evaluation of the tooth-composite interface and microleakage formation. 2,5,24,29,[34][35][36][37][38] This kind of experimental proof is, however, aimed at the comparative assessment of restoration systems that are investigated using the same laboratory standard, analogous to the rating of adhesive systems on the basis of bond strength values achieved within a single standardized trial.…”
Section: Introductionmentioning
confidence: 99%